Nucleolar dominance in triticales: control by unlinked genes - Neves, N. (1997)
Hybrid plants and animals often show suppression of activity of ribosomal genes (rDNA) originating from one of the parental or ancestral species. In the wheat6rye amphiploid triticale, containing 28 chromosomes of wheat origin and 14 from rye, rDNA of rye origin (on chromosome 1R) is not normally expressed, while the 1B- and 6B-origin rDNA from wheat shows strong expression. Expression of rDNA can be accurately assessed by the silver staining method, which stains both interphase nucleoli and metaphase rDNA sites that were actively expressed at the previous interphase. We show here that substitution of another rye chromosome, 2R, by a chromosome from hexaploid wheat, 2D (triticale-2D(2R)), prevents suppression of the rye-origin rDNA, and leads to activity of all six major rDNA loci. These results were found in two different triticales and supported by rDNA behaviour in wheat–rye chromosomal addition lines. Models for chromosomal interactions leading to control of rDNA expression are presented